In Vitro Antihypercholesterol Activity Test of Chocolate (Theobroma cacao L) Peel - Kusumaningtyas, Febrianika Ayu; Kadir, Sudirman A.; Djamal, Julia Megawati; Mantali, M. Fathurrachman (Majalah Farmaseutik, 2025)
Cholesterol is a lipid found in the blood and is not hydrolyzed, until now it has become a risk factor for Coronary Heart Disease (CHD). Reducing cholesterol levels is assisted by the use of antihypercholesterol drugs and natural medicines. The by-product of cocoa plantations (Theobroma cacao L) is skin containing secondary metabolites, including flavonoids, alkaloids, tannins and saponins. This study aims to identify the antihypercholesterol activity of cocoa fruit skin extract in vitro with the Liebermann-Burchard method using a UV-Vis spectrophotometer at a wavelength of 669nm. The test results showed that the ethanol extract of cocoa fruit skin obtained through maceration at concentrations of 10, 20, 40, 80 and 100ppm had the activity to lower cholesterol levels with an EC50 value of 67.785ppm. This activity is indicated based on the difference in color intensity of the test solution compared with control negative solution. The conclusion from the results obtained is that cocoa skin extract has activity as a natural cholesterol-lowering agent.